Impact of social capital towards strategic capabilities of manufacturing SMEs in Malaysia / Siti Normah Awang Tuah, Noor Hazlina Ahmad and Hasliza Abd Halim - Awang Tuah, Siti Normah; Ahmad, Noor Hazlina; Abd Halim, Hasliza (Center for Islamic Philanthropy and Social Finance (CIPSF), 2021)
Research on Malaysian SMEs has grown in significance amid SMEs contributions to the national income. Internationalisation of SMEs is imperative as smaller firms started to engage in international business develop their own capabilities and competitive advantage. Thus, it is important for SMEs in developing countries like Malaysia to look into their social capital and focus their efforts to strategize their capabilities to respond to the global competition and business opportunities. This study was conducted to examine the impact of social capital towards SMEs capabilities before they adopt the best strategic approach to face challenging situations. A quantitative approach was employed in this study and a total of 187 responses from manufacturing SME exporters were received and further analyzed using Partial Least Square (PLS) technique. The results demonstrated that social capital of manufacturing SMEs in Malaysia has significant impact only on innovation, marketing, and technology capabilities, but not market-linking and management capabilities.